“Elaboración de un sistema de gestión de inventarios para la Cruz Roja Ecuatoriana – junta Provincial de Tungurahua” - Caguasango Chanatasig, Doris Elizabeth (2023)
In the Ecuadorian Red Cross - Tungurahua Provincial Board, mismanagement of inventories and inadequate stock management in the warehouse of essential areas was evidenced, which is in charge of supplying ambulances belonging to the institution, despite the fact that it has a person in charge of logistics The objective of the present work is to elaborate an inventory management system for the improvement of the stock existence; This research is descriptive and the inductive method was used, the techniques to obtain information in the organization were direct observation in the warehouse, in the same way, an analysis of the problems found was carried out, followed by information collected in a database of existing inputs which was used to carry out the classification by the ABC probabilistic method, later, a stock control model was designed for the items that have been most in demand in the period of the year to then establish a model that best suits the characteristics and needs of the demand within the organization, specifically, the Economic Order Quantity (CEP) with safety stock.